2016
DOI: 10.1080/21691401.2016.1215327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated traditional Chinese and Western medicine therapy for acute hypertensive intracerebral hemorrhage: a meta-analysis

Abstract: Intracerebral hemorrhage (ICH) is an important public health problem associated with high mortality and morbidity. The aim of this study was to evaluate the clinical efficacy of integrated traditional Chinese (TCM) and Western medicine (WM) therapy for acute hypertensive ICH. Randomized controlled trials were searched in PubMed, Medline, Embase, Wanfang and CNKI database published between January 2000 and June 2016. Our results showed that integrated TCM and WM therapy appeared to be able to improve the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It contains two plants used in traditional Chinese medicine, rhubarb (Rheum palmatum L.), and peach seed (Prunus persica L. Batsch), and two animals used in traditional Chinese medicine, leeches (Whitmania pigra Whitman) and gadflies (Tabanus mandarinus Schiner). The Treatise on Cold Pathogenic Diseases pointed out that DDT has the efficacy to improve viscera and removes blood stasis, and it has been widely used to treat neurodegeneration and stroke in nowadays (Chen, 2012;Xu et al, 2015a;Xu et al, 2015b;Xu et al, 2016). In addition, previous clinical studies showed that promoting blood circulation for removing blood stasis therapy could effectively treat cerebral hemorrhage (Ma et al, 2011;Wang et al, 2013;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It contains two plants used in traditional Chinese medicine, rhubarb (Rheum palmatum L.), and peach seed (Prunus persica L. Batsch), and two animals used in traditional Chinese medicine, leeches (Whitmania pigra Whitman) and gadflies (Tabanus mandarinus Schiner). The Treatise on Cold Pathogenic Diseases pointed out that DDT has the efficacy to improve viscera and removes blood stasis, and it has been widely used to treat neurodegeneration and stroke in nowadays (Chen, 2012;Xu et al, 2015a;Xu et al, 2015b;Xu et al, 2016). In addition, previous clinical studies showed that promoting blood circulation for removing blood stasis therapy could effectively treat cerebral hemorrhage (Ma et al, 2011;Wang et al, 2013;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DiDang Tang (DDT) originates from Treatise on Cold Pathogenic Diseases , a Chinese traditional medicine formulary. It contains 2 Chinese traditional medicine plants, including rhubarb and peach seed , and 2 Chinese traditional medicine animals, leech , and gadflies , and it has been widely used to treat ICH patients and animal models (Li et al, 2015; Xu et al, 2015, 2017). Our previous study showed that DDT significantly reduced brain water content and intracerebral hematoma volume in rats with ICH by up-regulating the expression of brain-derived neurotrophic factor, tyrosine kinase B and vascular endothelial growth factor (VEGF) (Ren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the eld of traditional Chinese medicine (TCM), more and more attention was xed on the therapy of stroke, especially hemorrhagic stroke [8]. Song et al found that Naoxueshu oral liquid can signi cantly reduce the in ammation and edema of ICH [9].…”
Section: Introductionmentioning
confidence: 99%